The concept of people and new ideological concepts in Kazakhstan`s media - Orynkhanova G.A., Zadayeva A.A., V.I. Zhumagulova, G.A. Kazhigalieva, E.M. Khankishiyeva, (Opción, 2020)
The article deals with new and updated ideological concepts of Russian-language media in Kazakhstan, their linguistic and cognitive possibilities in the aspect of influence on public consciousness and its modernization. The basis of ideological concepts localization in the media is their clearly expressed axiological orientation and linguistic and cultural specificity, focus on the national consciousness. The value component of the key modernization concepts people, Mangilik El (eternal country) and Rukhani zhangyru (spiritual renewal) is analyzed.